2023
DOI: 10.1186/s12903-023-02984-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth structures and fixed appliances on automated cephalometric landmark recognition with a customized convolutional neural network

Abstract: Background One of the main uses of artificial intelligence in the field of orthodontics is automated cephalometric analysis. Aim of the present study was to evaluate whether developmental stages of a dentition, fixed orthodontic appliances or other dental appliances may affect detection of cephalometric landmarks. Methods For the purposes of this study a Convolutional Neural Network (CNN) for automated detection of cephalometric landmarks was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Table 1 presents the summarised studies on the application of AI in cephalometric analysis. In total, 23 articles were included based on both AI algorithms designed by their authors for the purpose of a specific study [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and web-based software available on search engines and mobile applications [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The studies focused on comparing the reliability of AI algorithms in localising cephalometric landmarks on lateral cephalometric radiographs with the manual tracing of these points; differences between various algorithms were also examined [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 presents the summarised studies on the application of AI in cephalometric analysis. In total, 23 articles were included based on both AI algorithms designed by their authors for the purpose of a specific study [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and web-based software available on search engines and mobile applications [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The studies focused on comparing the reliability of AI algorithms in localising cephalometric landmarks on lateral cephalometric radiographs with the manual tracing of these points; differences between various algorithms were also examined [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lowest accuracy was for the point Gonion, with 48.3% for the 2 mm error. Recently, Popova et al confirmed that the presence of orthodontic appliances did not significantly influence the performance of CNN-based open-source models, such as the Python programming language [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within AI, ML utilizes a set of inputs and outputs to create an algorithm to process the data and correctly predict the output [ 19 ]. AI and ML have been utilized for several tasks in orthodontics, such as for automated cephalometric analyses [ 20 , 21 , 22 , 23 , 24 ], predicting extraction vs. non-extraction treatment decisions [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], predicting orthodontic extraction patterns [ 34 ], determining the need for surgery in Class III patients [ 35 ], and growth assessment [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. However, little research has been conducted on the use of AI to predict mandibular growth.…”
Section: Introductionmentioning
confidence: 99%